First records of 31 species of butterflies and moths (Lepidoptera) in Cameroon, with remarks on their elevational ranges - Delabye, Sylvain; Maicher, Vincent; Sáfián, Szabolcs; Potocký, Pavel; Mertens, Jan E J; Przybyłowicz, Łukasz; Murkwe, Mercy; Kobe, Ishmeal N; Fokam, Eric B; Janeček, Štěpán; Tropek, Robert (Biodiversity data journal, 2020)
BACKGROUND: The biodiversity of West and Central Africa is understudied, including butterflies and moths (Lepidoptera). Cameroon, through its position in between few biogeographic regions and diversity of habitats, is an important hotspot of lepidopteran diversity. However, the country also ranks low when it comes to local biodiversity knowledge. During our long-term ecological projects in the Cameroonian part of the Gulf of Guinea Highlands, we collected rich material of butterflies and moths, including a number of interesting faunistic records. NEW INFORMATION: In this study, we report 31 species of butterflies and moths which have not yet been recorded in Cameroon. These species comprised eight new genera records for the country. In many cases, our records represented an important extension of the species' known distribution, including ten species whose distribution ranges extended into the Guinean biogeographic region. We also comment on the species' elevational distribution ranges on Mount Cameroon where most of our records originated. Additionally, we confirm the presence of a butterfly Telchinia encedena, after more than a century since its first and so far its only record in Cameroon.
Keywords: light-trapping; Mount Cameroon; Afrotropics; faunistics; Bamenda Highlands; bait-trapping